Preclinical Pharmacokinetics, Tissue Distribution, and Primary Safety Evaluation of Indo5, a Novel Selective Inhibitor of c-Met and Trks - Luo, Teng; Zhang, Fei-Xiang; Zhao, Ke; Gao, Hui-Ying; Zhang, Shou-Guo; Wang, Lin; Dou, Gui-Fang; Liu, Ting; Yu, Miao; Zhan, Yi-Qun; Chen, Hui; Yang, Xiao-Ming; et al. (Frontiers in Pharmacology, 2021)
The compound (3-(1H-benzimidazol-2-methylene)-5-(2-methylphenylaminosulfo)-2-indolone), known as Indo5, is a novel selective inhibitor of c-Met and Trks, and it is a promising anticancer candidate against hepatocellular carcinoma (HCC). Assessing the pharmacokinetic properties, tissue distribution, and toxicity of Indo5 is critical for its medicinal evaluation. A series of sensitive and specific liquid chromatography-tandem mass spectrometry methods were developed and validated to determine the concentration of Indo5 in rat plasma and tissue homogenates. These methods were then applied to investigate the pharmacokinetics and tissue distribution of Indo5 in rats. After intravenous injection of Indo5, the maximum concentration (Cmax) and the time at which Cmax was reached (Tmax) were 1565.3 ± 286.2 ng/mL and 1 min, respectively. After oral administration, Cmax and Tmax were 54.7 ± 10.4 ng/mL and 2.0 ± 0.48 h, respectively. We calculated the absolute oral bioavailability of Indo5 in rats to be 1.59%. Following intravenous injection, the concentrations of Indo5 in various tissues showed the following order: liver > kidney ≈ heart > lung ≈ large intestine ≈ small intestine ≈ stomach > spleen > brain ≈ testes; hence, Indo5 distributed highest in the liver and could not cross the blood–brain or blood–testes barriers. Continuous injection of Indo5 for 21 days did not lead to liver injury, considering unchanged ALT and AST levels, normal histological architecture of the liver, and normal number and frequencies of immune cells in the liver, indicating a very low toxicity of Indo5 in vivo. Collectively, our findings provide a comprehensive understanding of the biological actions of Indo5 in vivo and further support its development as an antitumor treatment for HCC patients.